Integrated network pharmacology and metabolomics to reveal the mechanism of QiShenYiQi Dripping Pills against cardiac structural and functional abnormalities - Zhang, Jun; Yang, Zunyuan; Jia, Xue; Li, Xinxin; Wang, Xiangyang; Rong, Hua; Liang, Yinan; Zeng, Wen; Jia, Wei; Ma, Xiaohui (Frontiers in Pharmacology, 2022)
Background: Heart failure (HF), the final stage of cardiovascular diseases, is a clinical syndrome of cardiac structural or functional abnormalities. QiShenYiQi Dripping Pills, short for QSYQ, showed effectiveness and safety in the treatment of HF according to modern pharmacological research and clinical studies, but the mechanism remains unclear. This study aims to clarify the mechanism of QSYQ in treating heart failure through the analysis to critical biomarkers, targets and pathways. Materials and Methods: In this study, the efficacies of QSYQ in non-human primates and rodents were evaluated, and the mechanism was demonstrated by integrating network pharmacology and metabolomics analysis. Furthermore, the targets from network pharmacology and the metabolites from targeted metabolomics were jointly analyzed to screen the critical pathways. Results: In rhesus monkeys with spontaneous chronic heart failure, nasogastric administration of QSYQ for 12 weeks caused profound improvement of systolic and diastolic function as evidenced by echocardiography detection. Consistently, QSYQ administration especially with higher dose lowered the blood pressure and improved the ventricular remodeling, collagen deposition and fibrosis markedly in Spontaneous Hypertension Rats (SHR) model. Computational prediction showed that QSYQ exhibited anti-HF effects possibly through HIF-1 signaling pathway, FoxO signaling pathway, TNF signaling pathway, PI3K-Akt signaling pathway and other enriched paths. Metabolomics analysis obtained 23 significantly altered metabolites, revealing that QSYQ significantly regulated the abnormal levels of fatty acids, carnitines, organic acids pyridines, nucleosides, which were mostly involved in myocardial energy metabolism related pathways. Conclusion: Based on serum and myocardium metabolomics and network pharmacology, the present study revealed that the actions of QSYQ in treating HF depend on multi-components, multi-targets and multi-pathways.